The Opportunity of Using Diode Laser with the Length of 1940 nm in the Treatment of Hemorrhoids - S. A. Frolov; A. M. Kuzminov; D. V. Vyshegorodtsev; O. A. Mainovskaya; Yu. L. Trubacheva; O. Yu. Fomenko; V. Yu. Korolik; I. S. Bogormistrov; I. A. Mukhin; A. M. Battalova; E. M. Bogdanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim: to improve the results of treatment of patients with hemorrhoidal disease of the 2nd and 3rd stages by using a diode laser with a wavelength of 1940 nm.Materials and methods. The study included 28 patients with hemorrhoids of the second or third stage. A new treatment method based on the use of a diode laser with a wavelength of 1940 nm was applied to all patients. This technique (laser hemorrhoidoplasty) provides for the thermal effect of laser radiation on the cavernous tissue of the internal hemorrhoid node and the terminal branches of the upper rectal artery. The intensity of postoperative pain syndrome was assessed and the clinical symptoms of hemorrhoidal disease manifestations were studied before and after surgery. To study the effectiveness of the proposed method and to assess the depth of thermal exposure to laser radiation, transrectal ultrasound with Dopplerography and pathomorphological examination were performed. The functional state of the rectal locking apparatus before surgery and in the postoperative period was assessed using sphincterometry. The quality of life of patients who underwent laser hemorrhoidoplasty was studied according to the SF 36 questionnaire.Results. Surgical intervention was performed under both local and spinal anesthesia. Intraoperative complications in the form of hemorrhoidal node bleeding were noted in 3 patients. In the early postoperative period, inflammatory edema of external hemorrhoids was diagnosed in 4 patients. The intensity of the pain syndrome was assessed on the VAS scale and by day 7 in 93 % of patients it did not exceed 1 point. All 28 patients were followed up within 1 to 6 months after the operation. All had no complaints characteristic of hemorrhoidal disease, no relapse of the disease was detected in any observation. Transrectal ultrasound with Dopplerography was performed, which made it possible to diagnose a 2–3-fold decrease in blood flow along the terminal branches of the upper rectal artery, and internal hemorrhoids determined earlier, before surgery, were not visualized already 1 month after surgery. According to sphincterometry, no violations of anal retention function were detected in all 28 patients.Conclusion. Surgical treatment of hemorrhoids of the 2nd and 3rd stages with the use of a diode laser with a wavelength of 1940 nm. with proper technical performance and the choice of optimal energy, it allows to achieve a good clinical effect. The proposed method of intervention ensures the absence of a pronounced pain syndrome, which does not lead to a significant decrease in the quality of life already in the early postoperative period and allows to shorten the period of labor rehabilitation. Laser hemorrhoidoplasty is a highly effective method of treating hemorrhoids at stages 2 and 3 of the disease and opens up the possibility of treatment on an outpatient basis.